(untitled) (Bangladesh Journal of Agriculture, 2026)
Estimating the carbon sequestration capacity of forest tree species is essential for implementing a massive plantation program in developing countries such as Bangladesh. The present study was conducted on the estimation of carbon storage and oxygen release capacity of Swietenia macrophylla and Eucalyptus camaldulensis, which were planted forest tree species in the same ecological condition. Allometric equations were applied to estimate organic carbon in two species of trees. The diameter increased with increasing height and positive correlations were found in S. macrophylla and E. camaldulensis, respectively (p < 0.05). The maximum carbon storage of S. macrophylla and E. camaldulensis were 17.24 kg tree-1 year-1 and 21.73 kg tree-1 year-1 at twenty-year-old trees, respectively. The lowest carbon storage of S. macrophylla and E. camaldulensis were 5.03 and 9.24 kg tree-1 year-1 at five years old, respectively. There was no significant difference (df=11; p=0.658) found between the DBH of the two species, while their DBH were significantly different among their ages (df=11; p=0.000). Besides, the height of these two species was significantly different (df=11; p=0.002) but not significant in their ages (df=11; p=0.694). The height and DBH growth became slower with the increase in the age of the plantations. The biomass, carbon stock, carbon dioxide storage, and O2 releasing potentiality were related to each other and significantly differed with their ages (p-value varied from 0.001 to 0.023). Comparatively higher growth performances were observed in E. camaldulensis than S. macrophylla in the same environmental conditions, management and equal ages. The findings indicated that S. macrophylla and E. camaldulensis can both be selected in the massive plantation programs in this area, which will contribute to large carbon storage and play a vital role in mitigating climate change. Bangladesh J. Agri. 2025, 50(2): 103-119